NEW-OLD CHALLENGES IN MANAGEMENT OF INDUSTRIAL ENTERPRISES NOWADAYS - OLEG Sukharev (Учёт. Анализ. Аудит)
The article investigates the state of the Russian industry by the most important development parameters (number of employees, structure of production costs, fixed assets, performance, etc.). The research shows that the structural problems accumulated in the Russian industry prevent industrial enterprises from further development and increasing their competitiveness. The main structural constraint of industrial development in Russia is an established dual model, where one group of sectors is highly profitable and has a relatively low risk while another group of sectors demonstrates low profitability with a high operating risk. The first group is represented by mining and transactional sectors, the second group includes industrial sectors. However, the existing industrial structure has in its framework its own group of such sectors. The presence of such structures results in the shift of resources to the most profitable sectors. The current structure of production costs and the low level of the overall technological effectiveness of production act as an additional structural constraint in the development of the manufacturing sector, including opportunities for conducting import substitution policy. Taking into consideration existing constraints, including the institutional conditions of industrial enterprises functioning, innovation development goals objectives cannot be an end in themselves, as their implementation along with possible improper setting of development priorities can impair the functioning of the industrial system. To avoid this, the author using the systemic approach to industrial policy offers certain tools of structural and institutional content to deal with the strategic tasks of manufacturing sectors development. First of all, it is necessary to purposefully shape the structure of industrial production by sectors taking into account not only the new priorities (technologies), but also the “old” technologies already in use. The above mentioned and other circumstances discussed in the article should be considered when introducing changes in the investment, tax and other types of policies and designing development programs.